Integrative analyses of Nervilia (Orchidaceae) section Linervia reveal further undescribed cryptic diversity in Thailand. Issue 4 (19th May 2018) - Gale, Stephan W.; Duangjai, Sutee; Li, Jihong; Ito, Yu; Watthana, Santi; Termwutthipreecha, Phatsara; Cheuk, Mang Lung; Suddee, Somran
Abstract : The delimitation of cryptic species is necessary to accurately classify and appropriately conserve biodiversity. Integrative analyses can be incisive in detecting and circumscribing cryptic diversity, especially in species complexes whose members are delineated by minor or overlapping morphological variation. We adopt an integrative approach to assess species relationships and resolve species boundaries in the taxonomically difficult Nervilia adolphi/punctata species alliance of N. sect. Linervia, an Old World complex of reduced, one-flowered terrestrial orchids that is both species-rich and poorly known in tropical and warm temperate Asia. We sampled 12 of the 27 known species of the alliance in Asia, including all four species reported from Thailand and a further 20 plants collected in that country that could not be satisfactorily identified using morphology alone. Phylogenetic analyses using one nuclear (ITS) and two plastid ( mat K and trn L-F) markers confirmed both N. sect. Linervia and the alliance itself as monophyletic, and corroborated 11 of the 12 sampled species; N. punctata proved polyphyletic, with the Thai samples referred to this Indonesian species falling sister to the Himalayan N. mackinnonii . The 20 unidentified Thai samples formed three distinct, strongly supported clades. STACEY, a Bayesian coalescence approach to species delimitation, resolved the same three clusters, but provided evidence suggesting that one comprised two distinct sub-clades. Building on this genetic evidence, we identify subtle morphological differences and invoke a diagnosable species concept to circumscribe three previously unrecognized cryptic species from Thailand. This objective approach to species delimitation validates ostensibly minor morphological differences as a basis for differentiating species within the alliance, paving the way for a global analysis of species boundaries throughout the genus as a whole.